ЛИНГВИСТИК ВА КАСБИЙ МУҲАНДИСЛИК БИЛИМЛАРИ ЧЕТ ТИЛИ КАСБИЙ КОММУНИКАТИВ КОМПЕТЕНТЛИГИНИНГ ТАРКИБИЙ ҚИСМИ СИФАТИДА - Қаршиева, Б.Ф. (SCIENCE and SOCIETY, 2022)
The article focuses on the stages of teaching English to non-English speaking students. The main principles to be followed in the article are minimalism, expediency of the topic, contextually and problematic. They were told to add the principle of focusing on the needs of students and the principle of activism.